A Novel Multisystem Proteinopathy Caused by a Missense ANXA11 Variant. Issue 2 (14th June 2021) - Leoni, Tauana Bernardes; González‐Salazar, Carelis; Rezende, Thiago Junqueira R.; Hernández, Ana Luisa C.; Mattos, Alexandre Hilário B.; Coimbra Neto, Antônio Rodrigues; da Graça, Felipe Franco; Gonçalves, João Pedro Nunes; Martinez, Alberto R.M.; Taniguti, Lucas; Kitajima, João Paulo; Kok, Fernando; et al.
Abstract : Objective: Protein misfolding plays a central role not only in amyotrophic lateral sclerosis (ALS), but also in other conditions, such as frontotemporal dementia (FTD), inclusion body myopathy (hIBM) or Paget's disease of bone. The concept of multisystem proteinopathies (MSP) was created to account for those rare families that segregate at least 2 out of these 4 conditions in the same pedigree. The calcium‐dependent phospholipid‐binding protein annexin A11 was recently associated to ALS in European pedigrees. Herein, we describe in detail 3 Brazilian families presenting hIBM (isolated or in combination with ALS/FTD) caused by the novel p.D40Y change in the gene encoding annexin A11 ( ANXA11 ). Methods: We collected clinical, genetic, pathological and skeletal muscle imaging from 11 affected subjects. Neuroimaging was also obtained from 8 patients and 8 matched controls. Results: Clinico‐radiological phenotype of this novel hIBM reveals a slowly progressive predominant limb‐girdle syndrome, but with frequent axial (ptosis/dropped head) and distal (medial gastrocnemius) involvement as well. Muscle pathology identified numerous rimmed vacuoles with positive annexin A11, TDP‐43 and p62 inclusions, but no inflammation. Central nervous system was also involved: two patients had FTD, but diffusion tensor imaging uncovered multiple areas of cerebral white matter damage in the whole group (including the corticospinal tracts and frontal subcortical regions). Interpretation: These findings expand the phenotypic spectrum related to ANXA11 . This gene should be considered the cause of a novel multisystem proteinopathy (MSP type 6), rather than just ALS. ANN NEUROL 2021;90:239–252